Fine‐Tuning of Sirtuin 1 Expression Is Essential to Protect the Liver From Cholestatic Liver Disease. Issue 2 (29th January 2019) - Blokker, Britt A.; Maijo, Monica; Echeandia, Marta; Galduroz, Mikel; Patterson, Angela M.; Ten, Anna; Philo, Mark; Schungel, Rebecca; Gutierrez‐de Juan, Virginia; Halilbasic, Emina; Fuchs, Claudia; Le Gall, Gwenaelle; et al.
Abstract : Cholestasis comprises aetiologically heterogeneous conditions characterized by accumulation of bile acids in the liver that actively contribute to liver damage. Sirtuin 1 (SIRT1) regulates liver regeneration and bile acid metabolism by modulating farnesoid X receptor (FXR); we here investigate its role in cholestatic liver disease. We determined SIRT1 expression in livers from patients with cholestatic disease, in two experimental models of cholestasis, as well as in human and murine liver cells in response to bile acid loading. SIRT1‐overexpressing (SIRT oe ) and hepatocyte‐specific SIRT1‐KO (knockout) mice ( SIRT hep–/– ) were subjected to bile duct ligation (BDL) and were fed with a 0.1% DDC (3, 5‐diethoxycarbonyl‐1, 4‐dihydrocollidine) diet to determine the biological relevance of SIRT1 during cholestasis. The effect of NorUDCA (24‐norursodeoxycholic acid) was tested in BDL/SIRT oe mice. We found that SIRT1 was highly expressed in livers from cholestatic patients, mice after BDL, and Mdr2 knockout mice ( Mdr2 –/– ) animals. The detrimental effects of SIRT1 during cholestasis were validated in vivo and in vitro . SIRT oe mice showed exacerbated parenchymal injury whereas SIRT hep–/– mice evidenced a moderate improvement after BDL and 0.1% DDC feeding. Likewise, hepatocytes isolated from SIRT oe mice showed increased apoptosis in response to bile acids, whereas a significant reduction was observed in SIRT hep–/– hepatocytes. Importantly, the decrease, but not complete inhibition, of SIRT1 exerted by norUDCA treatment correlated with pronounced improvement in liver parenchyma in BDL/SIRT oe mice. Interestingly, both SIRT1 overexpression and hepatocyte‐specific SIRT1 depletion correlated with inhibition of FXR, whereas modulation of SIRT1 by NorUDCA associated with restored FXR signaling. Conclusion: SIRT1 expression is increased during human and murine cholestasis. Fine‐tuning expression of SIRT1 is essential to protect the liver from cholestatic liver damage.